Moshe's Children : The Orphans of the Holocaust and the Birth of Israel - Luzzatto, Sergio, 1963- (Book collections on Project MUSE., 2023)
"Moshe's Children presents the inspiring story of Moshe Zeiri, a Jewish carpenter responsible for rescuing hundreds of Jewish refugee children who had survived the Final Solution. During the liberation of Italy, Zeiri, a volunteer in the British Army in Italy, assumed responsibility for and vowed to help around seven hundred Polish, Hungarian, Russian, and Romanian children. Although these orphans of the Shoah had been deprived of a family, a home, and a language and were irreparably robbed of their past, they were able to rebuild their lives through Zeiri's efforts as he founded the largest Jewish orphanage in postwar Europe in Selvino, Italy, where he began to rehabilitate the orphans and to teach them how to become citizens of the new nation of Israel. Moshe's Children also explores Zeiri's own story from birth in a shtetl to his upbringing and Zionist education, his journey to the Land of Israel, and his work there before the war. With narrative verve and scholarly acumen, Sergio Luzzatto brilliantly tells the gripping stories of these orphans of the Holocaust and the good man who helped point them to a real future"--